Multiple-Cylindrical Electrode System for Rotational Electric Field Generation in Particle Rotation Applications. (7th July 2015) - Benhal, Prateek; Chase, Geoffrey; Gaynor, Paul; Oback, Björn; Wang, Wenhui
Lab-on-a-chip micro-devices utilizing electric field-mediated particle movement provide advantages over current cell rotation techniques due to the flexibility in configuring micro-electrodes. Recent technological advances in micro-milling, three-dimensional (3D) printing and photolithography have facilitated fabrication of complex micro-electrode shapes. Using the finite-element method to simulate and optimize electric field induced particle movement systems can save time and cost by simplifying the analysis of electric fields within complex 3D structures. Here we investigated different 3D electrode structures to obtain and analyse rotational electric field vectors. Finite-element analysis was conducted by an electric current stationary solver based on charge relaxation theory. High-resolution data were obtained for three-, four-, six- and eight-cylindrical electrode arrangements to characterize the rotational fields. The results show that increasing the number of electrodes within a fixed circular boundary provides larger regions of constant amplitude rotational electric field. This is a very important finding in practice, as larger rotational regions with constant electric field amplitude make placement of cells into these regions, where cell rotation occurs, a simple task – enhancing flexibility in cell manipulation. Rotation of biological particles over the extended region would be useful for biotechnology applications which require guiding cells to a desired location, such as automation of nuclear transfer cloning.